LITERATURE REVIEW: THE INFLUENCE OF ECONOMIC LITERACY AND SOCIOECONOMIC STATUS OF PARENTS ON ENTREPRENEURIAL INTEREST - Safitri, Ayunda Elok; Kurniawan, Riza Yonisa; Majid, Mohamad Zuber Bin Abd (Journal of Education and Research, 2025)
The purpose of this literature review is to examine the influence of economic literacy and parental socioeconomic status on students' entrepreneurial interest. Economic literacy, which refers to an individual's ability to understand and apply economic concepts, plays a crucial role in shaping decisions and behaviors, especially in the context of entrepreneurship. The role of parents is also needed for someone in entrepreneurship. Preliminary research found that the majority of students have doubts about starting a business. The method used in this study is Systematic Literature Review (SLR). This study uses the Systematic Literature Review (SLR) method to analyze 11 articles from databases like Scopus, Google Scholar, and Google Cendekia, covering publications from 2020 to 2024. The inclusion criteria focused on peer-reviewed articles addressing the relationship between economic literacy, the socio-economic status of parents, and entrepreneurial interest, while studies without empirical evidence or directly related content were excluded. The review synthesized findings, revealing how socio-economic factors and economic literacy significantly influence entrepreneurial interest. Based on the review, the results indicate that there is a significant influence of economic literacy and parental socioeconomic status on entrepreneurial interest. Overall, this review emphasizes the importance of developing economic literacy and addressing socioeconomic disparities to encourage entrepreneurial aspirations among young people.